Risk-taking and self-harm behaviors as markers of adolescent borderline personality disorder - Blaha, Yasmine; Cavelti, Marialuisa; Lerch, Stefan; Steinhoff, Annekatrin; Koenig, Julian; Kaess, Michael (European child & adolescent psychiatry, 2024)
Adolescence is a critical period for early identification and intervention of borderline personality disorder (BPD). Risk-taking and self-harm behaviors (RSB) have been identified as promising early markers of BPD and correlates of depression in school-based samples. The present study aimed, first, to examine the association between RSB and BPD in a clinical sample of adolescents and, second, to examine whether RSB are also linked to depression. N = 405 participants (82.7% female) were recruited from an outpatient clinic for adolescents with RSB. RSB assessed included truancy, excessive media use, alcohol, tobacco, and illicit drug use, sexual risk-taking, and self-harm behavior. Regression analyses and generalized linear models were performed to examine the associations between individual RSB or patterns of RSB (identified using latent class analysis, LCA) and a diagnosis and severity of BPD or depression. All RSB (except excessive media use) were positively associated with BPD diagnosis and severity. In contrast, only non-suicidal self-injury (NSSI) and suicide attempts were positively associated with depression diagnosis and severity, while illicit drug use was negatively associated with depression severity. The LCA yielded two classes differing in the occurrence of RSB. The high RSB class was more likely to have a BPD diagnosis and greater BPD severity than the low RSB class. Classes did not differ regarding depression diagnosis or severity. As NSSI and suicide attempts were associated with both BPD and depression, the presence of additional RSB, besides self-harm behavior, may represent a specific risk marker for BPD in adolescents.
Online veröffentlicht: 09. Januar 2024
Gesehen am 06.05.2024